Effectiveness And Side Effects Of Alogliptin In Type 2 Diabetes Mellitus Patients. Article Review - Sinurat, Robert Tjayadi. S (Brawijaya University, 2019)
Diabetes mellitus is defined as a group metabolic disorders caused by multiple aetiology, characterized by hyperglycaemia with disorders of carbohydrate, protein and fat metabolism resulting from defects in insulin secretion, insulin action, or both. The clinical diagnosis of diabetes might manifest as polyuria, polydipsia, and unexplained weight loss, and is confirmed by measurement of abnormal hyperglycaemia. In type 2 diabetes progressive loss of b-cell insulin secretion often causes insulin resistance. Insulin resistance manifestations include increased lipolysis and free fatty acid production, increased hepatic glucose production, and decreased glucose intake to skeletal muscle. Alogliptin is an oral antidiabetic drug from class of dipeptidyl peptidase-4 (DPP-4) inhibitors for therapy in T2DM patients. Alogliptin can be used as monotherapy or combined with other anti diabetic agents such as metformin, sulfonylureas (glyburide), pioglitazone, and insulin. Based on several studies alogliptin shows low risk of the occurrence of side effects, such as hypoglycemia, edema, weight gain, RA, joint pain and cardiovascular events. The purpose of this review is to update clinical information about the effectiveness and side effects of alogliptin as diabetic therapy in T2DM patients.